Composing Monads v. Applicative Functors

There are several notions by which types of kind * -> * might “compose”. The more important one is you can compose them “sequentially”.

newtype Compose f g x = Compose { getCompose :: f (g x) }

Here you can see that Compose has kind (* -> *) -> (* -> *) -> (* -> *) much like any good composition of functors ought to.

So the question is: are there law-abiding instances like the following?

instance (Applicative f, Applicative g) => Applicative (Compose f g)
instance (Monad f,       Monad g)       => Monad       (Compose f g)

And the short answer as to why monads don’t compose as well as applicatives is that while the first instance can be written the second cannot. Let’s try!

We can warm up with Functor

instance (Functor f,     Functor g)     => Functor     (Compose f g) where
  fmap f (Compose fgx) = Compose (fmap (fmap f) fgx)

Here we see that because we can fmap an fmap-ed f we can pass it through the layers f and g like we need to. A similar game is played with pure

instance (Applicative f, Applicative g) => Applicative (Compose f g) where
  pure a = Compose (pure (pure a))

and while (<*>) appears tricky, if you look carefully it’s the exact same trick we used with both fmap and pure.

  Compose fgf <*> Compose fgx = Compose ((<*>) <$> fgf <*> fgx)

In all cases, we can push the operators we need “through” the layers of f and g exactly as we might hope.

But now let’s take a look at Monad. Instead of trying to define Monad via (>>=), I’m going to instead work via join. To implement Monad we need to implement

join :: Compose f g (Compose f g x) -> Compose f g x


join_f :: f (f x) -> f x  -- and
join_g :: g (g x) -> g x

or, if we strip off the newtype noise, we need

join :: f (g (f (g x))) -> f (g x)

At this point it might be clear what the problem is—we only know how to join consecutive layers of fs or gs, but here we see them interwoven. What you’ll find is that we need a commutativity property

class Commute f g where
  commute :: g (f x) -> f (g x)

and now we can implement

instance (Monad f, Monad g, Commute f g) => Monad (Compose f g)

with (the newtype agnostic) join defined as

join :: f (g (f (g x))) -> f (g x)
join fgfgx = fgx where
  ffggx :: f (f (g (g x)))
  ffggx = fmap commute fgfgx
  fggx :: f (g (g x))
  fggx = join_f ffggx
  fgx :: f (g x)
  fgx = fmap join_g fggx

So what’s the upshot of all this? Applicatives always Compose, but Monads Compose only when their layers Commute.

When can we commute layers? Here are some examples

instance Commute ((->) x) ((->) y) where
  commute = flip

instance Commute ((,) x) ((,) y) where
  commute (y, (x, a)) = (x, (y, a))

instance Commute ((->) x) ((,) y) where
  commute (y, xa) = \x -> (y, xa x)

-- instance Commute ((,) x) ((->) y) does not exist; try to write yourself!
-- OR:
-- It turns out that you need to somehow "travel back in time" to make it
-- work...
-- instance Commute ((,) x) ((->) y) where
--   commute yxa = ( ..., \y -> let (x, a) = yxa y in a )

Leave a Comment